ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN ULANG (Studi Kasus Pembelian Handphone Pada Mahasiswa Unisbank Semarang) (Students' Journal of Economic and Management, 2015)
This research are conducted to analyze the factors that influence consumers in making purchasing decisions again. The independent variables consist of Price (X1) and Quality Products (X2). The dependent variable is the Buying Decision Re (Y) Mobile on University Students Stikubank Semarang. The sample of 100 respondents were taken by using purposive sampling method. The analysis used is multiple regression analysis result, namely, Y = 0.303 + 0.457 X1 X2. The independent variables were the greatest influence on the dependent variable is the variable quality of the product (0.457), and was followed by a variable price (0,303). Deteminasinya coefficient (adjusted R2) of 0.432 or 43.2 percent. Quality Products showed the greatest regression coefficients. Product quality is the main factor affecting consumer purchase decisions over, and the price is a second factor influencing purchasing decisions reset. Keywords: price, quality product, repeat purchase decisions